Successful domestication of Neonothopanus Hygrophanus (Mont.) De Kesel & Degreef and Lentinus Squarrosulus Mont., indigenous saprophytic edible mushrooms from Kibira National Park in Burundi - Vincent Nteziryayo; Anthony M. Mshandete; Donatha D. Tibuhwa (CABI Agriculture and Bioscience)
Abstract Background Mushroom cultivation in Burundi provides an excellent way to diversify agricultural production although domestication of mushroom species is at an infancy stage. The country is endowed with indigenous forests that harbour a wide diversity of mushrooms with potential for domestication. This study was undertaken to explore opportunities for domestication of saprophytic wild edible mushrooms from the Kibira National Park (KNP) in Burundi. Methods Samples of Lentinus squarrosulus Mont. and Neonothopanus hygrophanus (Mont.) De Kesel & Degreef were collected from the field, and tissue cultured on Potato Dextrose Agar (PDA) medium. Spawn production and development was performed on sorghum grains and lignocellulosic substrates respectively and the parameters of mycelial growth and mushroom yield were determined. Results The germplasm of L. squarrosulus and N. hygrophanus was successfully isolated with an average tissue culture incubation time of 6.4 ± 0.54 days and 7.6 ± 0.54 days for L. squarrosulus and N. hygrophanus, respectively. Spawn production incubation time on sorghum grains was 12.6 ± 0.89 days and 14.8 ± 0.83 days for L. squarrosulus and N. hygrophanus, respectively. For full colonization of lignocellulosic substrates, spawn production time ranged between 19 ± 1 and 21 ± 1 days for L. squarrosulus and between 17 ± 1.22 and 18 ± 1.22 days for N. hygrophanus. Both species successfully produced fruiting bodies and mushrooms yielded at a rate of 18.24 ± 9.76 to 22.85 ± 9.16% for L. squarrosulus and 12.66 ± 8.95 to 15.3 ± 8.94% for N. hygrophanus which is here reported for the first time to be successfully domesticated. For both species, the cottonseed hulls substrate comparatively showed the best yield followed by the combination of maize cobs/soybean straws (MC + SBS) (50:50), the combination of rice straws/soybean straws (RS + SBS) (50:50) and the maize cobs substrate respectively, while the rice straw showed the least. The combinations of MC + SBS (50:50) and RS + SBS (50:50) showed a yield close to that of cottonseed hulls. Conclusions For the first-time, this study presents successful domestication of N. hygrophanus and L. squarrosulus from KNP. It is concluded that the substrates combinations used in the study give good yields, and therefore recommended for use as cost-effective and efficient alternative substrates.